Investigation of the interfacial energy level within organic semiconducting devices / Wong Wah Seng - Wong , Wah Seng (2021)
This main goal of this research is investigating the interfacial energy level of organic semiconducting devices by correlated to the devices performance as well as physical/chemical change in the blended/mixed organic semiconductor system. The first project reported the high efficiency extra warm white organic light emitting diodes (WOLEDs) by blending tris(4-carbazoyl-9-ylphenyl)amine (TcTa) to poly(vinylcarbazole) (PVK). The hole current for PVK:TcTa (60:40) increased by one order of magnitude in hole only device, but the current efficiency of WOLEDs improved only by 7% compared to pristine PVK. Using Ultraviolet photoelectron spectroscopy (UPS), it was discovered the hole injection barrier between poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) and PVK:TcTa blend was reduced by merely ~ 0.1 eV. Phase segregation of TcTa is observed using atomic force microscopy (AFM) resulting in percolation path which increases the hole current. However, using ultraviolet-visible (UV-Vis) spectroscopy the PVK:TcTa blend absorption was found redshifted with increasing TcTa suggesting the compactification of PVK which resulted in triplet quenching that limited the increase in current efficiency. The second project demonstrated the lowering of the work function of PEDOT:PSS by mixing with barium acetylacetonate (Ba(acac)2). The increasing pH, formation of precipitation, disappearance of PEDOT signature in UV-Vis spectroscopy suggested PEDOT was dedoped when mixed with Ba(acac)2. The work function of PEDOT:PSS was reduced from 4.9 eV to 3.6 eV upon mixing Ba(acac)2. The n-doped PEDOT:PSS increased the electron current density in electron only device due to the reduced electron injection barrier height. Both UPS and X-ray photoelectron spectroscopy (XPS) suggested the formation of barium polystyrene sulfonate (Ba-PSS) which resulted in the interfacial dipole up to 1.37 eV at indium tin oxide (ITO)/ Ba-PSS interface which result in reduction of PEDOT:PSS:Ba(acac)2 work function.